IMPLEMENTASI MODEL PEMBELAJARAN GUIDED INQUIRY DAN MIND MAPPING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS X PEMASARAN SMK BATIK 1 SURKARTA TAHUN AJARAN 2016/2017 - -, Raras Ayu Setyarini -; -, Bambang Wasito Adi -; -, Sunarto - (Jurnal Pendidikan Bisnis dan Ekonomi, 2017)
ABSTRACTRaras Ayu Setyarini K7413127. THE IMPLEMENTATION OF GUIDED INQUIRY AND MIND MAPPING LEARNING TO IMPROVE STUDENTS? ENGAGEMENT AND LEARNING OUTCOMES OF THE TENTH GRADE MARKETING STUDENTS OF SMK BATIK 1 SURAKARTA ACADEMIC YEAR 2016/2017. Thesis, Surakarta: Teacher Training and Education Faculty of Sebelas Maret University, Surakarta, December, 2017.The research aims to improve students? engagement and learning outcomes of the Introduction to Economics and Business lesson of the tenth grade marketing students of SMK Batik 1 Surakarta academic year 2016/2017 through the implementation of Guided Inquiry and Mind Mapping Learning. This research is a Classroom Action Research (CAR) which was conducted in two cycles. Each cycle consist of planning, acting, observing, and reflecting. The subject of this research was 42 students at tenth grade of SMK Batik 1 Surakarta. The data sources came from teachers and students. The main techniques of data collection were using observation and test. Meanwhile, the supporting techniques were using interviews, documentations, and archives. The data was analyzed by using quantitative and qualitative analysis techniques. The results of this research showed that the implementation of Guided Inquiry and Mind Mapping Learning can improve the students? engagement and learning outcomes of the Introduction to Economics and Business lesson of tenth grade marketing students which can be seen at the students learning outcomes from pre-cycle, cycle I, until cycle II activities. The students? engagement showed at 35,71%  in pre-cycle which improves to 83,33% in cycle I, and improves to 90,47% in cycle II. The students? learning outcomes showed an improvement that can be seen from the students? mean score from 57,11%  in pre-cycle which improves to 71,43%  in cycle II, and improves to 90,48% in cycle II.  ABSTRAKRaras Ayu Setyarini K7413127. IMPLEMENTASI MODEL PEMBELAJARAN GUIDED INQUIRY DAN MIND MAPPING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS X PEMASARAN SMK BATIK 1 SURAKARTA TAHUN AJARAN 2016/2017. Skripsi, Surakarta : Fakultas Keguruan dan ilmu Pendidikan Universitas Sebelas Maret Surakarta, Desember 2017.Penelitian ini bertujuan meningkatkan keaktifan dan hasil belajar mata pelajaran pengantar ekonomi dan bisnis siswa kelas X Pemasaran SMK Batik 1 Surakarta tahun ajaran 2016/2017, melalui implementasi model pembelajaran Guided Inquiry dan Mind Mapping. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Setiap siklus terdiri atas perencanaan, pelaksanaan tindakan, observasi dan refleksi. Subyek penelitian adalah siswa kelas X SMK Batik 1 Surakarta sebanyak 42 anak. Sumber data berasal dari guru dan siswa. Observasi dan tes digunakan sebagai teknik utama, sementara wawancara, dokumentsi, dan arsip digunakan sebagai teknik pendukung . Teknik analisis data yang digunakan adalah  analisis data kuantitatif dan anlisis datab kualitatif.Hasil penelitian menunjukkan bahwa penerapan model pembelajran Guided Inquiry dan Mind Mapping dapat meningkatkan keaktifan dan hasil belajar mata pelajaran pengantar ekonomi dan bisnis siswa kelas X Pemasaran, mulai dari hasil belajar siswa dari kegiatan pra siklus, siklus I, sampai siklus II. Kekatifan siswa pada tahap pra siklus menunjukkan prosentase 35,71%  meningkat menjadi 83,33%  pada siklus I dan kembali meningkat menjadi 90,47% pada siklus II. Hasil belajar siswa menunjukkan peningkatan dari nilai yang diatas KKM yaitu 57,11%  pada pra siklus meningkat menjadi 71,43%  pada siklus I dan kembali meningkat menjadi 90,48% pada siklus II.